2018
DOI: 10.7287/peerj.preprints.3471
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vertical stratification of plant-pollinator interactions in a temperate grassland

Abstract: 11Interactions between plants and their pollinators vary in time and space at different scales. A neglected aspect of small-scale variation of plant-pollinator interactions is the role of vertical position of flowers. We conducted a series of experiments to study vertical stratification of plant-pollinator interactions in a dry grassland. We observed flower visitors on cut inflorescences of Centaurea scabiosa and Inula salicina placed at different heights above ground in two types of surrounding vegetation: sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Indeed, their generalist behaviour, at the species level, could be the result of individually specialized diets, since most pollen retrieved on hoverfly individuals usually comes from a single plant taxon (Lucas et al ) and depends on flower availability and phenology (Cowgill et al , Colley and Luna , Lucas et al ). Moreover, some hoverflies have preferences regarding plant colour, morphology and inflorescence height (Branquart and Hemptinne , Colley and Luna , Lunau , Klecka et al , b).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, their generalist behaviour, at the species level, could be the result of individually specialized diets, since most pollen retrieved on hoverfly individuals usually comes from a single plant taxon (Lucas et al ) and depends on flower availability and phenology (Cowgill et al , Colley and Luna , Lucas et al ). Moreover, some hoverflies have preferences regarding plant colour, morphology and inflorescence height (Branquart and Hemptinne , Colley and Luna , Lunau , Klecka et al , b).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, hoverflies seem to visit mostly open bowl-shaped flowers ( Branquart & Hemptinne, 2000 ), where they feed on both nectar and pollen ( Gilbert, 1981 ), but some of them have relatively long proboscises which allow them to reach nectar even in flowers with relatively long spurs ( Gilbert, 1981 ; Vlašánková et al, 2017 ). In addition, inflorescence height also affects flower visitation by some species ( Gervasi & Schiestl, 2017 ; Klecka, Hadrava & Koloušková, 2017 ). It has been recently demonstrated that selective flower visitation by hoverflies can exert a selection pressure strong enough to cause rapid evolutionary shifts in multiple plant traits ( Gervasi & Schiestl, 2017 ; Zu & Schiestl, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pollinator's attraction to a plant depends on visual cues indicating high floral reward such as the number of open flowers (Akter et al, 2017) and the size of floral display (Biella et al, 2019), and on the amount and quality of nectar and pollen (Cresswell, 1999;Grindeland et al, 2005), along with general conspicuousness of the plant which increases its detection by potential pollinators, such as plant height (Junker et al, 2013;Klecka et al, 2018a;Hernández-Villa et al, 2020), local plant clustering (Elliot & Irwin, 2009;Akter et al, 2017), and flower colour (Reverté et al, 2016). Our experiments showed that, these morphological trait differences among the plants had a cascading effect on the number and identity of flower visitors of S. alba and on its reproduction.…”
Section: Impact On Pollination and Seed Productionmentioning
confidence: 99%
“…Flower visitation rate of insect-pollinated plants depends on visual cues indicating high floral reward such as the number of open flowers (Conner and Rush, 1996;Akter et al, 2017) and the size of floral display (Grindeland et al, 2005;Parachnowitsch et al, 2010;Biella et al, 2019), and on the amount and quality of nectar and pollen (Cresswell, 1999;Grindeland et al, 2005). Other morphological features can also influence plant detection by potential pollinators, such as plant height (Junker et al, 2013;Klecka et al, 2018a;Hernández-Villa et al, 2020), local plant clustering (Elliot andAkter et al, 2017), and flower colour (Reverté et al, 2016). Measurements of flower visitation with plants grown in the spring 2017 and plants grown in the summer 2018 revealed that and in both cases plants grown with higher amount of water had a significantly higher number of flower visitors compared to plants grown under low amount of water irrespective of nitrogen supply.…”
Section: Impact On Pollination and Seed Productionmentioning
confidence: 99%